Qualitative Infrastrukturszenarien für die deutsche Energiewende: Integration von Akteuren und Institutionen in langfristige Technologiezukünfte. 8- Energie, Wirtschaft und Gesellschaft. Who puts the German Energiewende into action? Characterizing arenas of change and implications for electricity infrastructure. - Schmid, Eva; Knopf, Brigitte; Pechan, Anna (My University, 2015)
Germany s energy system is in a state of transition known as the Energiewende, targeting a competitive low-carbon economy until 2050. Existing mitigation scenarios for Germany describe technological transitions that are driven primarily by exogenous assumptions; little reference is made to the questions of why and how this change comes about and which actors and institutions are decisive in this process. We contribute to filling this gap. Based on a comprehensive literature review we characterize arenas of change in the German electricity system by specifying key actors, their motives and activities and infer implications for the electricity infrastructure of the future. A synthesizing discussion illustrates that the question of how to transform the German electricity infrastructures is ultimately a question of values that need to be resolved in public debate. However, a long latency period in grid-based infrastructure development posits limits on the kind of Energiewende that can be realized in the decade to follow. Based on this characterization of the actor landscape, future research will develop qualitative infrastructure scenarios by engaging the important actors which have been identified.
Keywords: Energie; Alternativenergie; Energiepolitik; Energiekonzept; Energiewende; Erneuerbare Energie; Akteur